1998
DOI: 10.1016/s0140-6736(00)80011-2
|View full text |Cite
|
Sign up to set email alerts
|

Randomised trial of growth hormone in short normal girls

Abstract: Growth-hormone therapy effectively increased height SD score among short normal girls started on treatment in early to mid childhood, with no untoward effect on pubertal progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 0 publications
4
63
1
Order By: Relevance
“…Inclusion criteria for participants were broadly similar, specifying short normal children less than the 3rd percentile in height, with no chronic illness or dysmorphic syndromes. Five studies 23,[38][39][40]43 included children who were prepubertal, and two studies 37,41 had pubertal children, one of which included girls only. 37 Six of the trials 23,37-41 compared GH-treated children with untreated controls, with an additional treatment group receiving luteinising hormone-releasing hormone analogue (LHRHa) to delay puberty in one trial, 41 and an additional group of patients who did not give consent to randomisation in another trial.…”
Section: Rctsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inclusion criteria for participants were broadly similar, specifying short normal children less than the 3rd percentile in height, with no chronic illness or dysmorphic syndromes. Five studies 23,[38][39][40]43 included children who were prepubertal, and two studies 37,41 had pubertal children, one of which included girls only. 37 Six of the trials 23,37-41 compared GH-treated children with untreated controls, with an additional treatment group receiving luteinising hormone-releasing hormone analogue (LHRHa) to delay puberty in one trial, 41 and an additional group of patients who did not give consent to randomisation in another trial.…”
Section: Rctsmentioning
confidence: 99%
“…Five studies 23,[38][39][40]43 included children who were prepubertal, and two studies 37,41 had pubertal children, one of which included girls only. 37 Six of the trials 23,37-41 compared GH-treated children with untreated controls, with an additional treatment group receiving luteinising hormone-releasing hormone analogue (LHRHa) to delay puberty in one trial, 41 and an additional group of patients who did not give consent to randomisation in another trial. 37 Two studies 42,43 were placebo controlled, with an additional observation group in one.…”
Section: Rctsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies related to the effect of treatment with growth hormone on the adult height of children with ISS with a total sample size of 1,517 were included in the meta-analysis ( Fig. 1 and Table 1 [10,11,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] When results of studies were combined using random effects model, SMD for treatment start height was -1.64 (95% CI: -2.01 to -1.28) which is equal to 5% (their height was higher than 5% of participants) (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in the past, many children with idiopathic short stature received GH treatment despite a lack of definitive evidence for its efficacy. A meta-analysis (19), which included one small randomized trial (20) and three studies with non-randomized, untreated controls, reported a 5-6 cm difference in adult height between treatment (mean GH dose, 0.31 mg/kg per week) and control groups.…”
Section: Efficacy Of Gh Treatment In Issmentioning
confidence: 99%